Corrosion inhibition of 6061 aluminium alloy in marine environments by milk - Mohd Zulkarnain, Zulkifli (2010)
6061 aluminium alloy is an important material with wide ranges of industrial applications and marine technology. This study examines the use of milk for improvement of corrosion resistance of 6061 aluminium alloy in sodium chloride. Weight loss method and potentiodynamic polarization measurement were employed to study the corrosion behavior of 6061 aluminium alloy in sodium chloride. The weight loss method showed that the presence of milk significantly decreases the corrosion rates of 6061 aluminium alloy 6061 in the test solutions. Pitting corrosion take places in all the specimens during immersion test and the pitting can be seen through surface analysis by using optical microscope 200x magnifications. With the presence of milk in the sodium chloride, the pitting growth is smaller and lesser compare to no milk added. The electrochemical measurements also showed the similar finding that the presence of milk reduces the corrosion rates, and that corrosion current densities (icorr) simultaneously increases the values of polarization resistance Rp. The inhibition efficiencies increase with increasing of milk concentration. The nature of adsorption of milk on the metal surface has also been examined. Scanning electron microscope (SEM) and energy dispersive x-ray spectroscopy (EDS) confirmed the formation of thin film on the metal surface, which reduces the overall corrosion reaction.